Comparison of Data Mining Algorithms for Predicting the Cancer Disease Using Python - Mehdi, Mehtab; Pahwa, Kanika; Sharma, Bharti (2019 8th International Conference System Modeling and Advancement in Research Trends (SMART), 2019)
Fundamentally, machine learning is the part of data science which is nothing but AI. We use machine learning algorithms for predicting the future results after analyzing the past data. This technique of data processing is called data analytics. Machine Learning algorithms are divided in three sections: Supervised, Unsupervised and Reinforcement. These algorithms are further subdivided in other sections. In this paper we are comparing these algorithms by which in future we could easily update the accuracy level of the ML algorithms. For doing this we used the healthcare data which has been uploaded on the kaggle. We implemented the machine learning algorithm using python programming language and calculated the accuracy level of each algorithm.